Algorithm for the management of ectropion through medial and lateral canthopexy - Siook Baek; Jae-Ho Chung; Eul-Sik Yoon; Byung-Il Lee; Seung-Ha Park (Archives of Plastic Surgery, 2018)
Background Patients with ectropion experience devastating symptoms. Therefore, the preventionand management of this condition are of utmost importance. To treat ectropion, it is important to perform medial and lateral canthopexy in an effective way. In this study, we propose a comprehensive algorithm for the prevention and management of ectropion based on a new classification of ectropion according to its signs and causes.